(untitled) (International Journal of Environmental Sciences, 2025)
Introduction: Sleep disturbances during pregnancy are a common concern, potentially harming both mother and baby, as disrupted sleep patterns can affect their health and well-being, leading to adverse obstetric outcomes by stimulating inflammatory pathways, including increased IL-6 production. Aim: To evaluate the prevalence and age-related differences in sleep deprivation among pregnant women in their second or third trimester. Materials and methods: A cross-sectional survey was conducted among 320 pregnant women aged 18-32 years in their second or third trimester, recruited from the obstetrics and gynaecology (OG) inpatient department of MGMCRI using convenience sampling. Participants were categorized into two age groups (18-25 and 26-32 years). The study included low-risk primigravida women who could read and write in Tamil or English, while excluding those with a history of infertility or multigravida status. After obtaining ethical approval and informed consent, sleepiness was evaluated using the Epworth Sleepiness Scale (ESS), which demonstrated high internal consistency (Cronbach’s alpha = 0.88). The ESS scores (0-24) classified sleepiness levels from normal to severe, with scores above 10 indicating excessive daytime sleepiness. The findings showed a significant prevalence of sleep deprivation among the participants. Results: The study examined sleep deprivation in pregnant women using the Epworth Sleepiness Scale (ESS). Group 1 (G1; n=162, mean age 23.71 ± 1.45) and Group 2 (G2; n=158, mean age 27.98 ± 1.64) showed varying ESS scores across trimesters. Severe sleepiness was reported in 22% of G1 and 20% of G2, while moderate sleepiness was common in both groups. G2 had a higher proportion of normal sleepers (27%) than G1 (23%). Across trimesters, G1 showed more moderate sleepiness in the third trimester (48%) than in the second (41%), while severe sleepiness decreased. G2 had more severe cases in the third trimester (27%) compared to the second (20%). These results highlight age and trimester-related variations in sleep patterns during pregnancy. Conclusion: The survey revealed a high prevalence of Maternal sleep deprivation and it can impact both maternal and fetal health. Yoga may serve as a non-pharmacological intervention to improve sleep quality by reducing stress, anxiety, and physical discomfort. Further research using randomized controlled trials is recommended to assess the effectiveness of yoga in improving sleep across pregnancy.